Extraction, structural properties, and applications of pullulan - Jha A.; Kumar M.; Bharti K.; Mishra B. (My University, 2025)
Pullulan is a biodegradable, linear, unbranched, and hydrophilic fungal exopolysaccharide commercially produced by the strains of yeast-like polymorphic fungi Aureobasidium pullulans. Structurally composed of repeating units of maltotriose connected by α-(1→6) glycosidic bonds, this arrangement provides this polysaccharide with two unique characteristics: structural flexibility and increased solubility. The presence of reactive hydroxyl groups allows structural modifications and functionalization in the basic polysaccharide structure using various conjugation techniques, thus providing a range of potential applications as a biomaterial in the pharmaceutical and biomedical fields. This chapter offers a thorough illustration of the production and extraction of pullulan, its structural properties, and its application in the development of various pharmaceutical dosage forms for the administration of bioactive molecules to the target site via various routes of administration. © 2023 Elsevier Inc. All rights reserved.